Pengaruh Pemberian Photosynthetic Bacteria (PSB) dan Pupuk NPK Majemuk Terhadap Pertumbuhan dan Hasil Produksi Tanaman Rosella - Ratih Kurniasih; Rofhik Azhar; Putri Irene Kanny (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2026)
Rosella is a shrub that has potential as an industrial and pharmaceutical raw material. Rosella production in Indonesia remains relatively low, at only 2-3 tons per hectare, while plant quality is declining due to continuous inorganic fertilization. This study aims to determine the effect of providing photosynthetic bacteria (BPS) and compound NPK fertilizer. This research was conducted for 6 months from January to June 2025 in the rosella land of Gunadarma University Technopark Cianjur using a 2-factorial Randomized Completely Block Design (RCBD). The first factor is photosynthetic bacteria with 4 levels, namely without PSB/Control (P0), PSB 5 ml/L (P1), PSB 10 ml/L (P2), PSB 15 ml/L (P3) and the second factor is compound NPK, namely NPK 11,5 g/plant (N1), NPK 17 g/plant (N2), NPK 22,5 g/plant (N3). There were 12 treatment combinations which were repeated 3 times and there were 4 samples so there were 144 experimental units. The parameters observed include growth and production results. Growth parameters include plant height, number of primary branches, and number of productive branches, while yield parameters include fresh fruit weight per plant, fresh fruit calyx weight per plant, dry fruit weight per plant, and dry fruit calyx weight per plant. The data obtained were analyzed using ANOVA at 5% level and further tested using the DMRT test. The results of the study showed that photosynthetic bacteria had a significant effect on plant height, number of productive branches, and dry weight of fruit per plant, while compound NPK fertilizer only had a significant effect on plant height. The results showed no interaction between photosynthetic bacteria and compound NPK on all parameters. Keywords: Photosynthetic bacteria, compound NPK, functional microbes, rosella